A Supporting Design Method When Longwall FaceStrides across and Passes through a Roadway. (19th October 2020) - Pan, Weidong; Li, Xinyuan; Li, YiWei; Li, Xiaobin; Qiao, Qing; Gong, Haoran
Abstract : In coal underground mining, situation of longwall face striding across (SAR) or passing through roadway (PTR) is very common, especially in an inclined coal seam mining. A roadway supporting design method, consisting of a model using to determine the minimal rock strata thickness and a segmental supporting scheme, is developed. In addition, to represent the mechanical behaviour of the caved material authentically, an elastic model was developed. The results showed that the elastic model has a good agreement with the caved material mechanical behaviours at a relatively lower stress condition. By using a FDEM method, a real case in Xutuan coal mine is studied. Compared with the process without backfill, the z -displacement of cross-cut roof decreased shapely after backfilling, with a maximum z -displacement, decreases from 0.76 m to 0.13 m and from 0.39 m to 0.064 m in PTR and SAR section, respectively. Therefore, the possibility of fall of ground (FOG) and crushing accidents can be reduced effectively with backfilling material of wood cribs. And the maximum subsidence (SAR section side) of face floor is 0.16 m, which is small enough to ensure normal production. The results of this study are likely to be useful as a reference for the safe and efficient mining of coal resources under similar conditions.